Transport hubs of the Crimean region and Ukrainian SSR in terms of infrastructure development after the Second World War - Pavel Satsky (Facta Simonidis)
It is common knowledge that in 1954 the Crimean Region of the Russian SFSR was transferred to the Ukrainian SSR. There were numerous speculations about its legal aspect. Nowadays, the current need is to analyze the social and economic preconditions for making the decision on the transfer of the Crimean region from Russia to Ukraine, and there were plenty of them. This article presents the prospects for the development of rail communication between the Crimea and Ukraine which were planned before 1960. The plans for the development of rail communication between the Crimea and mainland Ukraine had economic and military-strategic factors. They provided the prospect of a drastic increase in transportation loads. The active development of agriculture and industry on the territory of the Ukrainian SSR, extensive construction of the channels and irrigation systems, construction of a military base in Sevastopol, as was foreseen by the plans for social and economic development, became the preconditions for the planned growth of transportation loads between the Crimea and Ukraine and stimulated the development of rail communication between the Ukrainian SSR and the peninsula. It must be separately noted that the plans for the development of recreational resources of the Crimean peninsula stimulated not only the development of connection between Ukraine and the Crimea but also the development of transport in the Crimea itself.